Information and Communications Technology for Teacher Training in India - Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
Information and Communications Technologies (ICTs) are making major differences in the teaching approaches and the way students are learning. ICT enhanced learning environment facilitates active, collaborative, creative, integrative, and evaluating learning as an advantage over the traditional methods. Overtime, we have learnt that integrated teacher education initiatives brought more learning resources to the classroom. The new technologies and their effective integration with curriculum and classroom processes have presented enormous possibilities and have revolutionized teacher education at all levels. The recent ICT developments have allowed teachers to be imaginative, flexible, and willing to renew their vision of teaching and learning. The possibilities of integrating ICT tools by teachers and for in-service training and teachers' professional developments have undergone a revolution in the last decade. New Educational technologies in India have encouraged the adoption of new roles by the teachers to embrace new pedagogies and approaches. The New Education Policy 2020, gives immense importance to the interdependence of education and technology in the future. It emphasizes the role of ICT as an effective tool in facilitating teacher education and encourages the utilization of technology platforms for online teacher training. The policy calls for investment in digital infrastructure, development of online teaching platforms and tools, creation of virtual labs and digital repositories, training teachers to become high-quality online content creators, designing and implementing online assessments, establishing standards for content, technology, and pedagogy for online teaching-learning. ICT integration for pre-service teacher training programs plays a crucial to equip and prepare future teachers for the classroom, who are confident and competent about managing the change and influencing it for the better quality of teaching. Considering the future of using technology for teaching and learning is always ever-evolving and challenging. Teacher Education Institutes must create an environment for teachers to enable them to create an appropriate learning experience for teachers to enable them to create an appropriate learning experience for students in the new age of learning.
Keywords: 330